Halal topic journal content analysis in Journal of Islamic Marketing, British Food Journal and Meat Science / Muslim Ismail@Ahmad … [et al.] - Ismail@Ahmad, Muslim; Ismail, Mohd Nasir; Othman, Roslina; Ismail, Mohd Saufi (Academy of Contemporary Islamic Studies (ACIS), Universiti Teknologi MARA (UiTM), 2019)
Journal of Islamic Marketing, British Food Journal and Meat Science are among the most productive journals publication in halal research. Data collection is from Scopus database, set for all available documents in each respective journals. This research utilized bibliometric analysis of three journals content with description of journal metric. Citation data from respective journals are extracted from Scopus database. Co-word or co-occurrence of terms from respective data collection is analyzed and visualized using bibliometric software. The descriptive study of data citation aimed to extract valuable insight into halal research indexed in Scopus. Dataset in Journal of Islamic Marketing was 280 citations from 2010 to 2019. British Food Journal data (from 2010-2019) was 1,361 citations and Meat Science data was 1,852 citations (from 2014-2019). Scopus’s CiteScore, Scimago Journal Rank (SJR) and Source Normalized Impact per Paper (SNIP) is used to measure the journals. Papers of the highest citation each of respective journals from 2016-2018 are highlighted. This research utilizes VOSviewer for data visualization and GEPHI for data statistical analysis of words co-occurrence in titles and abstracts. This research aims to analyze content in three journals specifically to identify subject relations or subject clusters in the article journals in 8 years span.